Hedges and Boosters in Undergraduate Thesis Abstracts of Qomaruddin University Students - Eva Nur Mazidah; Wiwik Indah Cahyani; Lailatul Masruroh (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
In writing abstracts, authors usually include metadiscourses such as hedges and boosters. This study aims to compare the use of hedges and boosters in writing undergraduate thesis abstract as a mean of communicative strategy to increase or decrease the strength of the statement. This research data was taken from 25 undergraduate thesis abstract of English Language Education Study Program and 25 from Mathematic Study Program at Qomaruddin University Gresik with 100-250 word range and analyzed based on Hyland's taxonomy (2005).The results showed that there were 22 variants of hedges words with a total use of 53 words and 17 variants of boosters words with a total use of 130 words. In the undergraduate thesis abstract, the students of the English Language Education Study Program dominantly use hedges words, such as in the adverb and verb classes. However, for the use of hedges words in undergraduate thesis abstracts, Mathematic Study Program students are more dominant than English Language Education Study Program students even though the word variants used are still dominated by English Language Education Study Program students, such as in the verb class. In addition, students using hedges have greater value than boosters in writing undergraduate thesis abstracts as a way to reduce the risk of opposition, to show courtesy and to obscure authorship and strengthen opinions. Boosters are also used to demonstrate the originality of research. Hedging by the students shows that there is a lack of knowledge of English rhetoric. Thus, the use of hedges and boosters can also help to improve students’ academic writing skills.